THE INFLUENCE OF ICONIC AND CULTURALLY ROOTED POLICE BUILDINGS ON PUBLIC TRUST: A QUALITATIVE STUDY AT THE TANJUNG BATU POLICE SECTOR - Syaparudin Akso (PAPATUNG: Jurnal Ilmu Administrasi Publik, Pemerintahan dan Politik, 2025)
Public trust in the police institution is a crucial element in maintaining social order and institutional legitimacy. In recent years, efforts to humanize public services through architectural design have gained increasing attention, particularly amid growing public skepticism toward the Indonesian National Police (Polri). This study aims to explore how iconic police building designs rooted in local culture influence public trust through symbolic and cultural representation. A qualitative approach with a single-case study design was employed, focusing on the Integrated Police Service Center (SPKT) of the Tanjung Batu Police Sector, which features distinctive architectural elements such as traditional roof structures, local wood materials, and regional cultural ornaments. Data were collected through in-depth interviews, field observations, and visual documentation. The findings reveal that these architectural elements foster emotional connection, a sense of comfort, and public perceptions of openness and professionalism within the police institution. These results highlight the importance of integrating local identity into public service infrastructure design as a strategic effort to build public trust and strengthen institutional credibility.